MAKING CREATIVE INDUSTRIES POLICY: THE MALAYSIAN CASE - Barker, Thomas; Lee, Yuen Beng (Universiti Sains Malaysia, 2017)
With the launch of the Dasar Industri Kreatif Negara (DIKN) document in 2009, the creative industries have become a policy focus area for the Malaysian government in line with Wawasan 2020 (Vision 2020). By critically analysing the institutional background of the DIKN and creative industries policies implemented to date, this paper shows how the DIKN has been translated into subsequent policy. This paper argues that creative industries policy has largely narrowed to funding schemes and resulted in a proliferation of government agencies. Due in part to the legacy of the Multimedia Super Corridor (MSC) and Multimedia Development Corporation (MDEC), "digital" has increasingly come to be synonymous with "creative". We argue that this raises questions as to how the creative industries are perceived and supported and ultimately the meaning of creativity in the Malaysian creative industries policy context